2018
DOI: 10.35724/mujagri.v1i1.1299
|View full text |Cite
|
Sign up to set email alerts
|

Kelayakan Usahatani Bawang Merah Di Distrik Tanah Miring

Abstract: The objective of this research is to setimate cost, revenue, profit, and the feasibity of redonion farming in Tanah Miring District. The method use primary and secondary data. All the redonion farms (46 famers) in Tanah Miring District become free responden. Data analisis used costanalisis, R/C ratio and BEP (Break Event Point) analisized. The result showed that red onion farmingin Tanah Miring District have the cost Rp. 23.526.255 for 3 (three) month in 0,3 ha. The revenueof red onion farming is Rp. 45.738.74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Metode yang diterapkan dalam penelitian ini adalah rumus kelayakan usahatani menggunakan R/C ratio (Ena et al, 2021;Rasmikayati et al, 2021;Soekartawi, 2006). (Suratiyah, 2015) Keterangan Untuk rata-rata biaya variabel yang dikeluarkan usahatani sawi keriting adalah sebesar Rp15.010.618/per tahun.…”
Section: Tc = Fc + Vcunclassified
“…Metode yang diterapkan dalam penelitian ini adalah rumus kelayakan usahatani menggunakan R/C ratio (Ena et al, 2021;Rasmikayati et al, 2021;Soekartawi, 2006). (Suratiyah, 2015) Keterangan Untuk rata-rata biaya variabel yang dikeluarkan usahatani sawi keriting adalah sebesar Rp15.010.618/per tahun.…”
Section: Tc = Fc + Vcunclassified
“…In 2018 Kelyum et al [8] has conducted research on the development of onion cultivation in Merauke Regency, finding that several factors that cause very low production yields are planting media, weather, and maintenance. Meanwhile, the results of direct interviews that we conducted in July-August 2020, with several onion farmers in Merauke Regency also showed that there were five problems faced by onion farmers including: 1. lack of knowledge about cultivation techniques; 2. poor soil conditions for planting onions; 3. changes in the weather in the field; 4. appropriate volume of water for onion plants; 5. maintaining stable temperature and humidity in the onion cultivation areas.…”
mentioning
confidence: 99%